Lecturers’ electronic briefcase: an elevation of electronic teaching portfolio (E-TP) / Tengku Intan Suzila T.S ... [et al.] - T.S., Tengku Intan Suzila; A.N., Jelani; M.N., Mohd Yusri; K.F., Yusob (2020)
Digital document management system (DDMS) has been promoted as a part of the green movement. DDMS can also be adapted to suit the education field. A digital based standardized digital teaching portfolio is highly anticipated to suit safe-keeping, auditing and promotional purposes thus Electronic Teaching Portfolio (e-TP) was materialized in 2019. At present, Lecturers’ Electronic Briefcase (LEB) is an improved product of e-TP. It is a boost to DDM among lecturers. The problems that lead to LEB innovation was e-TP could not allow ease of access to lecturers without requesting permission from the developers, huge cloud management and auditors’ accessibility issues. The objective of LEB is to simplify developers’ accountabilities, hand over the responsibility of safe-keeping teaching evidences (TE) to the lecturers, allow private access to auditors. Findings suggest that e-TP can be improved by promoting the use of LEB.